Analysis of needs for development of animated video learning media arina expressions based on local wisdom Kediri SDN Burengan II Kediri - Lukita Oktalia, Elza; Laila, Alfi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research aims to (1) describe the obstacles in developing learning media for animated videos of Arina's expressions based on Kediri local wisdom; (2) describe the need for developing Indonesian language learning media for class II; (3) describe the supporting capacity for developing learning media for animated videos of Arina's expressions based on Kediri local wisdom. The method used in the research was descriptive qualitative with the research subjects being class II students at SDN Burengan 2 with a total of 60 students and 2 teachers at SDN Burengan 2. Data collection techniques used interviews, questionnaires and observation. The analysis technique used is the data triangulation analysis technique (Mills and Huberman) with the stages of data collection  data reduction  data presentation  drawing conclusions. The research results show that 1) There are several obstacles in implementing animated video media, namely teachers prefer textual learning (relying only on textbooks), teachers are not very proficient in operating IT, teachers are more comfortable teaching without using learning media, and teachers still have difficulties in finding suitable media for students. 2) The development of animated video learning media is really needed by class II students at SDN Burengan 2. 3) The supporting capacity in implementing IT-based media is that the principal has facilitated computers and LCDs in implementing IT-based media, the principal provides facilities to help teachers be creative in making media learning, and school principals facilitate workshops/training in making IT-based media such as animated videos. From the results of this research, it is necessary to continue with further research in the form of developing animated video media for Arina's expressions based on Kediri local wisdom at SDN Burengan II Kediri.